111 An audit of headache referrals from primary care, and subsequent management in the outpatient clinic. Issue 12 (14th November 2019) - Fernandes, Linford; Tanti, Matthew; Randall, Marc; Cosgrove, Jeremy
Abstract : Background: Headache is the most common reason for referral to a neurology outpatient clinic but many headaches can be managed in primary care. Methods: We audited 100 consecutive headache referrals against Leeds Teaching Hospitals NHS Trust (LTHT) referral criteria and the Neuro Network Vanguard (NNV) headache pathway. Results: The mean age was 41 years (range 16 -90), 67% were female and 31% had previously seen a neurologist for headaches. Referrals were appropriate in 44% and 49% according to LTHT and NNV guidelines, respectively. Migraine was the suspected diagnosis in 50% of referrals - half of these tried two or more preventative medications. The clinic consultations of 89 of the 100 referrals were reviewed: 72% were diagnosed with migraine (of which 53% were chronic). Following consultation, migraine was the final diagnosis in 49% of referrals that proposed an alternative diagnosis; 9% referred as suspected migraine received a different diagnosis. Conclusion: Less than half of the referrals received were appropriate according to LTHT and NNV criteria. Migraine was the major referral reason and ultimate diagnosis. Empowering primary care to manage migraine is an urgent local priority and may reflect a national issue.